Fully hydrogenated vegetable oil-based non-dairy creamer intake impairs athletic performance in mice: serum metabolomics and intestinal microbiota analyses - Xu, Shi Qi; Gong, Wenchao; Li, Jing; Qin, Wenjie; Dang, De Xin; Yu, Yanming; Chung, Dong-Hwa (Frontiers in Nutrition, 2026)
IntroductionFully hydrogenated vegetable oil-based non-dairy creamer (FHVO-NDC) is produced through complete hydrogenation of vegetable oil, resulting in a trans fat-free product commonly incorporated into sports foods and performance-oriented beverages. Because diet plays a crucial role in shaping athletic performance, understanding the potential physiological effects of FHVO-NDC is essential for athletes and fitness enthusiasts. However, the combined impact of FHVO-NDC on muscle physiology, serum metabolomic alterations, and gut microbiota has not been evaluated. Therefore, the objective of this study was to address this knowledge gap using a controlled mouse model.MethodsExperimental animals were assigned to two groups: a control group receiving regular water and a treatment group receiving water supplemented with FHVO-NDC. Multiple physiological and biochemical parameters were monitored, including body condition (n = 8), feeding behavior (n = 4), athletic performance (n = 8), myofiber characteristics (n = 6), muscle fatigue-related biochemical indicators (n = 6), serum metabolite profiles (n = 5), and intestinal microbiota composition (n = 5). Data were analyzed using one-way ANOVA to determine statistical significance.ResultsFHVO-NDC intake did not alter body condition or feeding behavior. However, it resulted in a measurable decline in athletic performance. This reduction was accompanied by decreased myofiber diameter (p < 0.001), reduced muscle glycogen content (p < 0.001), and lower levels of key enzymes associated with muscle fatigue (p ≤ 0.001). Additionally, FHVO-NDC consumption led to a significant increase in the abundance of the genus Alistipes (p = 0.007) and elevated levels of serum 2-fluoronicotinic acid (p = 0.022), both of which have been linked to impaired muscle function and metabolic dysregulation.DiscussionCollectively, these findings suggest that FHVO-NDC consumption may exert detrimental effects on muscle physiology and athletic performance in the mouse model. The observed alterations in muscle traits, serum metabolites, and gut microbiota highlight potential biological mechanisms through which FHVO-NDC could negatively influence exercise capacity, warranting further investigation regarding its implications for athletes and physically active individuals.